2013
DOI: 10.1080/03602559.2013.832853
|View full text |Cite
|
Sign up to set email alerts
|

The Crystallinity Behavior of Polyethylene/Clay Nanocomposites Under the Influence of Water-Assisted Melt Blending

Abstract: High-density polyethylene (HDPE)/clay nanocomposites were prepared via water-assisted and conventional melt blending. The influence of exfoliated/intercalated domains on crystallinity of nanocomposites was then investigated. X-ray diffraction and electron microscopy evidenced for enhanced intercalation and partial exfoliation of clay platelets pursuing rheological measurements. The methane permeability of water-injected nanocomposites was lower compared to melt-blended specimens implying the influence of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, the physical properties of polyethylene terephthalate (PET) were studied by Rostogi [11] , and it was considered that both the rigid amorphous layer and crystallites should be introduced to interpret the effect of the microstructure on the macroproperties of polymers. Research by Esteki et al [12] also reported that the mechanical properties of nanocomposites were not influenced by the degree of crystallinity and crystal thickness and the role of crystalline regions on the mechanical properties of polyethylene=clay nanocomposites was somehow overshadowed by the degree of particle-polymer interaction as well as intercalation status.…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
“…Moreover, the physical properties of polyethylene terephthalate (PET) were studied by Rostogi [11] , and it was considered that both the rigid amorphous layer and crystallites should be introduced to interpret the effect of the microstructure on the macroproperties of polymers. Research by Esteki et al [12] also reported that the mechanical properties of nanocomposites were not influenced by the degree of crystallinity and crystal thickness and the role of crystalline regions on the mechanical properties of polyethylene=clay nanocomposites was somehow overshadowed by the degree of particle-polymer interaction as well as intercalation status.…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
“…This was attributed to the fact that at higher filler loadings the crystallinity of PA6 chains is determined mostly by the nanoclay dispersion . It should be emphasized that the processing circumstances can also impose serious impact on the crystallization behavior of the assigned systems . Bearing in mind that the presence of nanoclay puts serious limits on the mobility of polymer chains during melt processing, one comes to the conclusion that the state of intercalation and exfoliation plays an important role in such systems .…”
Section: Introductionmentioning
confidence: 99%
“…Research studies dealing with crystallinity of nanocomposites have shown two opposite roles for nanoparticles. At low nanoparticle loadings, percentage crystallinity of nanocomposites increases because of the role of nanoparticles as heterogeneous nucleating agents, while a further increase of the nanoparticle contents results in a decline of crystallinity, as a result of growth retardation . In first case, the nanoparticle's surface acts as a heterogeneous nucleation site by lowering the barrier energy against nucleation, which generates finer and more crystals.…”
Section: Resultsmentioning
confidence: 99%